Additional Evidence for X-Y Chromosome Interchange in a 46,XX Male - BUTLER, MERLIN G. (Nebr Med J, 1980)
Evidence is presented to support a possible X-Y chromosome interchange etiology for the rare infertile 46,XX male syndrome. Cytogenetic studies including various chromosome banding techniques on lymphocytes and fibroblasts revealed the absence of a Y chromosome in the 400 early metaphase and midmetaphase chromosome plates analyzed. Measurements of the X chromosomes of this patient showed a significant difference in length between the terminal unstained bands on the short arms designated as p22 of the two X chromosomes. The difference was also significant when compared to the same type of measurements of the X chromosomes from normal females.